Students’ Reading Anxiety and Comprehension in An Indonesian Madrasah: A Correlational Case Study - Nuri Oktaviani Sakinah; Hasan Basri (Universitas Islam Negeri Madura, 2025)
The capacity to extract information from written texts and exhibit knowledge or comprehension of that information is known as reading comprehension. The word